(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
The heterogeneity of Indonesian residents is a necessity that often causes social conflict. One of them is the difference in the meaning of religious texts which leads to exclusive movements in the name of religion. This paper wants to offer a practical offer of religious moderation to reduce social conflict in the name of religion by examining Q.S. al-Baqarah [2]:142-143 maqashidi interpretation perspective. This study uses the library method. The data were processed using descriptive-analytical techniques to be explored and interpreted later. The results are 1) through this verse, Allah implicitly says to stay away from the character of sufahā, namely to deny the truth out of interest; 2) the term wasath in Q.S. al-Baqarah [2]: 142-143 interpreted as a balance in all aspects of life with the principle of moderation; and 3) This verse places a person who has wasath character at the highest level, namely being a role model for the people and has the right to decide matters in society